Immunohistochemical and genetic analysis of osteoclastic giant cell tumor of the pancreas - Lukás, Zdenek; Dvorák, Karel; Kroupová, Iva; Valásková, Iveta; Habanec, Boris (Pancreas, 2006)
Clinical, histopathologic, immunohistochemical, and genetic analyses of 2 osteoclastic giant cell tumors of the pancreas are presented. The neoplasms were composed of osteoclastic giant cells and pleomorphic cells (PCs). The tissue-specific markers gave evidence of mesenchymal nature of the osteoclastic giant cells, as well as other components of the tumor, and lacked any signs of epithelial differentiation in both patients. The nonepithelial nature of both components in the osteoclastic giant cell tumors presented may be associated with a better prognosis, which corresponds to the previous reports of similar neoplasms. A positive immunoreactivity to neuron-specific enolase was recorded in patient 2. The presence of CD68 in osteoclastic giant cells proved their histiocytic nature. Both components of the tumors showed a negative immunoreactivity to desmin and only a scattered reactivity to smooth muscle cell actin, typical markers of myofibroblastic differentiation. Mutation analysis of the tumor revealed the wild state of both p53 and K-ras oncogenes in both patients. A positive immunoreactivity for p53 in PCs of both osteoclastic giant cell tumors was recorded, whereas osteoclastic giant cells did not express this protein. The expression of p21 was recorded in osteoclastic giant cells in patient 1. The absence of Ki-67 in the osteoclastic giant cells and its expression in PCs gave evidence of a different proliferation rate of both cell populations. Different tissue-specific markers, a different proliferation rate, and a different state of oncogene activation in the osteoclastic giant cell tumors contribute to the idea that the tumor derives from a pluripotent cell that may differentiate into an array of phenotypes.
Keywords: dospělí; antigen Ki-67; nádory obrovskobuněčné; Cyclin-Dependent Kinase Inhibitor p21; Tumor Suppressor Protein p53; Proliferating Cell Nuclear Antigen; Female; proliferační antigen buněčného jádra; Adult; ženské pohlaví; Pancreatic Neoplasms; Osteoclasts; Giant Cell Tumors; Immunohistochemistry; lidé; nádory slinivky břišní; imunohistochemie; osteoklasty; Male; inhibitor p21 cyklin-dependentní kinasy; nádorový supresorový protein p53; Ki-67 Antigen; lidé středního věku; mužské pohlaví; Middle Aged; Humans